SOCIAL CLASS AND CLASS STRUGGLE IN SUZANNE COLLINS’S THE HUNGER GAMES - MOH. ARIFIN (LITERA KULTURA : Journal of Literary and Cultural Studies, 2015)
Abstrak Perjuangankelasadalahmasalah yang selalumunculdalamsejarahperjalananmanusia, bahkandalamkehidupanmasyarakat modern perjuangankelasmasihdapatditemui.Dalam novel The Hunger GameskaryaSuzanne Collins, diceritakanduakelompokmasyarakat yang masing-masingmewakiliduakelas yang berbedadalamstruktur social masyarakat.MerekaadalahCapitol sebagaikaumpemilik modal yang memilikikuasadankekayaan, sehinggamerekabebasmelakukanapapun demi kepentinganmereka.Sebaliknya, masyarakatdistrik 12 sebagaikelasbawahtidakmemilikiapapun.Fakta-fakta yang muncultersebutmelatarbelakangimasalah-masalah yang munculseperti(1) bagaimanakehidupankelas-kelas social digambarkandalam novel The Hunger Gameskarya Suzanne Collins ? Dan (2) bagaimanaperjuangankelasdapatmunculdalam novel The Hunger Gameskarya Suzanne Collins? Metode yang digunakanadalahhermeneutika yang jugasekaligussebagaiteknik, sedangkanpendekatan yang digunakanadalahpendekatanpragmatik.Hasil yang didapatkanakanmenjelaskanbahwakeduakelompokmasyarakat yang berbedaterlibatdalamkonflik yang berkepanjangan. Kaumproletarselalumenjadiobyekeksploitasibagikaumborjuis.Tetapihalinilah yang memunculkankesadarankelasbagikaumproletar, sehinggaperjuangankelasakanmunculsebagaibentukperlawananterhadapkaumborjuis. Padaakhirnyakaumproletarharusbersatuuntukmenghancurkanmusuhmerekayaitukapitalisme yang di bawaolehkaumborjuis.Merekaharusmelenyapkankepemilikanpribadiuntukmewujudkanmasyarakattanpakelas. Kata Kunci: marxisme, perjuangankelas, dankelassosial Abstract Class struggle has a very real existence in modern society. In Suzanne Collins’s The Hunger Games there are two different classes in Panem social structure. The Capitol as a representative of the bourgeoisie and District 12 become representatives of the proletariat. The Capitol as the owner of the mode of production has wealth and power. It is make them able to do anything they want. While District 12 is the lower classes who do not have anything. They can only work for the bourgeoisie to survive. Based on that presumptively facts, problems arise along with questionings, which are delivered to two main questions of (1) How is social class depicted in Suzanne Collin’s The Hunger Games ?and (2) How does class struggle rise in Suzanne Collins’s The Hunger Games ? The used method must not get rid of hermeneutics, the approach is classified to pragmatics, while the technique scopes on the way of interpretations work on. As the result describes that different social class bring both parties engage in sustainable conflict. The proletariat as the powerless one was oppressed by bourgeois, they become object of exploitation. This raises their class consciousness. And lead to the emergence of the class struggle among them. Lastly, proletariat must unite in order to destroy their real enemy, capitalism, which was brought by the bourgeoisie. They have to abolish private property in order to establish classless society. Keywords: Marxism, class struggle, and social class